The Interplay of Climate Change and Health: Addressing Physical and Mental Well-Being (Ricos Biology, 2024)
Climate change has been recognized as one of the most significant global challenges with far-reaching implications for human health, particularly in the domain of chronic diseases and mental health. This paper aims to explore the relationship between chronic diseases and climate change, explaining how recent academic research relates global changes in the climate to human health, including mental well-being. An in-depth review of literature has been carried out to explore the links between climate change and chronic diseases, its underpinning mechanisms explaining these relationships, identification of vulnerable populations, and interpretation of findings in the public health contexts of policy and intervention. The paper also provides a comprehensive theoretical framework addressing aspects of chronic diseases, mental health, and climate change. Overall, findings show that climate change has drastic impacts on the burden, distribution, and incidence in the management and progression of chronic diseases, along with significant implications for mental health. This overview therefore emphasizes that climate change is, without doubt, an issue of great importance and needs to be at the forefront for interventions among healthcare providers, policymakers, and researchers in efforts to manage the arising burden of chronic diseases and improve general health. This paper points out the high necessity of interdisciplinary collaboration in the development of adaptive strategies, improving health resilience, and applying preventive measures that can effectively support responses to the health challenges emanating from climate change, particularly in the context of mental health. It also emphasizes the importance of mainstreaming consideration of climate into the public health planning process, medical education, and response to chronic illness so that healthcare systems are well-prepared for the new health environment occurring in a changing climate.